Proceedings of the IGSHPA Research Track 2018 2018
DOI: 10.22488/okstate.18.000025
|View full text |Cite
|
Sign up to set email alerts
|

Video inspection of wells in open loop ground source heat pump systems in Norway

Abstract: This paper presents results from video inspections of groundwater wells in Melhus and Elverum, in Norway. The method has identified iron hydroxides, bacterial growth and sand production as causes of clogging in different wells. Video inspection has proven itself a reliable, inexpensive and quick method for such investigations. The videos supply documentation for the building owner about the well condition. A video inspection should be incorporated as a standard part of the tender document and an integrated par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The location of the pump high above the production well screen is a possible gas exsolution trigger. The current well design is not able to prevent gas bubbles from escaping the well bore [4]. If these gases are pH-regulating, e.g., CO 2 , the design might facilitate alterations of the groundwater chemistry and trigger precipitation reactions.…”
Section: Discussion and Comparison Of Design And Design Toolsmentioning
confidence: 99%
See 3 more Smart Citations
“…The location of the pump high above the production well screen is a possible gas exsolution trigger. The current well design is not able to prevent gas bubbles from escaping the well bore [4]. If these gases are pH-regulating, e.g., CO 2 , the design might facilitate alterations of the groundwater chemistry and trigger precipitation reactions.…”
Section: Discussion and Comparison Of Design And Design Toolsmentioning
confidence: 99%
“…All of the seven re-injection systems have experienced clogging of the injection well screen [5]. The clogging material is often a mixture of sediments and precipitated hydroxides [3,4]. Inspections of the systems have shown that re-injection of groundwater is done without a backpressure technique, and vacuum pressures have been observed in the re-injection pipeline in several installations.…”
Section: Current Investigations In Melhusmentioning
confidence: 99%
See 2 more Smart Citations
“…However, by identifying which of the four major components that are affected, the test results enable the operator to plan necessary maintenance to the affected components without having to spend time on unaffected parts of the system. The cause of the problem can then be identified through other means, such as by video inspection of the affected wells or pipes (Gjengedal et al 2018). Furthermore, the operator is able to investigate how effective the maintenance has been by conducting the same test procedure after the maintenance and comparing the results.…”
Section: Discussionmentioning
confidence: 99%